Exploring residents' satisfaction of facilities provided by private apartment companies - Rahman, Muhammad Sabbir; Hussain, Bashir; Uddin, ANM Meshquat; Islam, Nazrul (National Cheng Kung University, 2015)
In recent times, Bangladesh has faced serious housing problems, especially for people who live in cities. In response, this study examines the relationship between housing expenses, affordability, service quality, hygienic conditions, and community attachment and residents' satisfaction, respectively. A questionnaire-based survey was carried out with customers in the major parts of Dhaka, Bangladesh. In addition to descriptive analysis, other statistical analyses, such as exploratory factor analysis, confirmatory factor analysis, and a structural equation modeling approach were used to test the hypotheses. The findings reveal that there is a strong relationship between services provided by the private companies and residents' satisfaction, with hygienic conditions playing a major role. This study also confirms a significant relationship between housing expenses and residents' satisfaction when affordability plays a mediating role. This study is the first of its kind, to the best of our knowledge, conducted on the customers of the Bangladeshi housing industry. The contribution of this study is the construction of a research theoretical framework that potentially highlights the perceived satisfaction or dissatisfaction of residents with the facilities provided by the private apartment owners in Bangladesh.